Clopidogrel metaboliser status based on point-of-care CYP2C19 genetic testing in patients with coronary artery disease - Erlinge, David; James, Stefan; Duvvuru, Suman; Jakubowski, Joseph A.; Wagner, Henrik; Varenhorst, Christoph; Tantry, Udaya S.; Brown, Patricia B.; Small, David; Moser, Brian A.; Sundseth, Scott S.; Walker, Joseph R.; Winters, Kenneth J.; Gurbel, Paul A. (Thrombosis and Haemostasis, 2014)
We compared results obtained with the Nanosphere Verigene® System, a novel point-of-care (POC) genetic test capable of analysing 11 CYP2C19 variants within 3 hours, to an established, validated genotyping method (Affymetrix™ DMET+; reference assay) for identifying extensive and reduced metabolisers of clopidogrel. Based on genotyping, patients (N=82) with stable coronary artery disease on clopidogrel 75 mg daily were defined as extensive metabolisers (*1/*1, *1/*17, *17/*17), reduced metabolisers (*1/*2, *1/*8, *2/*2, *2/*3), or of indeterminate metaboliser status (*2/*17). Pharmacokinetic exposure to clopidogrel’s active metabolite and pharmacodynamic measures with P2Y12 reaction units (PRU) (VerifyNow® P2Y12 assay) and VASP PRI (PRI) were also assessed. There was a 99.9% overall concordance of marker-level data between the Nanosphere Verigene and DMET+ systems in identifying the CYP2C19 variants and 100% agreement in classifying the patients as extensive (n=59) or reduced metabolisers (n=15). Extensive metabolisers had significantly higher active metabolite exposure than reduced metabolisers (LS means 12.6 ng*h/ml vs 7.7 ng*h/ml; p<0.001). Extensive metabolisers also had lower PRU (LS means 158 vs 212; p=0.003) and VASP PRI (LS means 48% vs 63%, p=0.01) compared to reduced metabolisers. Rates of high on-treatment platelet reactivity were higher in reduced metabolisers compared to extensive metabolisers (VASP PRI ≥50%: 79% vs 47%; PRU >235: 33% vs 16%). The Nanosphere Verigene CBS system identified 11 CYP2C19 alleles in less than 3 hours with a high degree of accuracy when compared to a conventional method, and was further validated against pharmacokinetic and pharmacodynamic phenotypes.
Keywords: Genotyping techniques; clopidogrel; prasugrel; pharmacogenetics CYP2C19 polymorphisms